Pengaruh Diversifikasi Sumber Dana Dan Efisiensi Pengelolaan Anggaran Terhadap Mutu Pendidikan Di PAUD Swasta - Fitri Wulandari; Nur Intan Rochmawati (Literasi: Jurnal Pendidikan Guru Indonesia, 2026)
This study investigates the influence of funding diversification and budget management efficiency on the quality of early childhood education in private PAUD institutions in Pangkalan Banteng District, Kotawaringin Barat Regency, Central Kalimantan. The background of this research lies in the financial challenges faced by private PAUD institutions, which often rely heavily on tuition fees as their primary source of funding, making them vulnerable to fluctuations in student enrollment and parents’ ability to pay. The objectives of this study are to analyze the effect of funding diversification, budget efficiency, and their simultaneous impact on educational quality. This research employs a quantitative approach with regression analysis, involving 60 respondents consisting of principals and treasurers from 30 private PAUD institutions. Data were collected through questionnaires and documentation during the 2025/2026 academic year. The findings indicate that funding diversification has a significant positive effect on educational quality, while budget efficiency also contributes substantially to improving institutional performance. Furthermore, the simultaneous influence of both variables demonstrates that sustainable financial management is crucial to enhancing the quality of early childhood education services.